Elevation, temperature, and aquatic connectivity all influence the infection dynamics of the amphibian chytrid fungus in adult frogs. - Sarah J Sapsford (Public Library of Science (PLoS), 2013)
Infectious diseases can cause population declines and even extinctions. The amphibian chytrid fungus, Batrachochytrium dendrobatidis (Bd), has caused population declines and extinctions in amphibians on most continents. In the tropics, research on the dynamics of this disease has focused on amphibian populations in mountainous areas. In most of these areas, high and low elevation sites are connected by an assemblage of streams that may transport the infectious stage of the pathogen from high to low elevations, and, also, this pathogen, which grows well at cool temperatures, may persist better in cooler water flowing from high elevations. Thus, the dynamics of disease at low elevation sites without aquatic connections to higher elevation sites, i.e., non-contiguous low elevation sites, may differ from dynamics at contiguous low elevation sites. We sampled adult common mistfrogs (Litoria rheocola) at six sites of three types: two at high (> 400 m) elevations, two at low elevations contiguous with high elevation streams, and two at low elevations non-contiguous with any high elevation site. Adults were swabbed for Bd diagnosis from June 2010 to June 2011 in each season, over a total of five sampling periods. The prevalence of Bd fluctuated seasonally and was highest in winter across all site types. Site type significantly affected seasonal patterns of prevalence of Bd. Prevalence remained well above zero throughout the year at the high elevation sites. Prevalence declined to lower levels in contiguous low sites, and reached near-zero at non-contiguous low sites. Patterns of air temperature fluctuation were very similar at both the low elevation site types, suggesting that differences in water connectivity to high sites may have affected the seasonal dynamics of Bd prevalence between contiguous and non-contiguous low elevation site types. Our results also suggest that reservoir hosts may be important in the persistence of disease at low elevations.